(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article analyzes the linguopoetic features of toponyms in the novel "Avlodlar dovoni". It examines their role in constructing historical authenticity of the Mughal Empire period, shoping national and cultural color, conveying symbolic meaning and revealing characters psychology. The study concludes that toponyms function as significant poetic elements within the artistic structure of the novel.